Fabrication and characterization of sub-micron and nanoscale structures in commercial polymers - Ibrahim, Fathima Shaida (Kansas State University, 2010)
This dissertation describes the fabrication and characterization of nanoscale structures in commercially available polymers via multiphoton ablation and bottom-up self assembly techniques. High-resolution surface imaging techniques, such as atomic force microscopy (AFM) and chemical force microscopy (CFM) were used to characterize the physical features and chemical properties, respectively, of these nanoscale structures. Fabrication using both top-down and bottom-up methods affords flexibility in that top-down allows random, user-defined patterning whereas bottom-up self assembly produces truly nanoscale (1-100nm) uniform features. Multiphoton induced laser ablation, a top-down method, was used to produce random sub-micron scale features in films of poly(methylmethacrylate) (PMMA), polystyrene (PS), poly(butylmethacrylate) (PBMA) and poly[2-(3-thienyl)ethyloxy-4-butylsulfonate] (PTEBS). Features with 120-nm lateral resolution were obtained in a PMMA film which was concluded to be the best polymer for use with this method. It was also found that etching resolution was highest for polymers having high glass transition temperatures, low molecular weights and no visible absorption. Bottom-up self assembly of polystyrene-poly (methylmethacrylate) (PS-b-PMMA) diblock copolymer and UV/acetic acid treatment produced nanoscale cylindrical domains supported by a substrate. AFM imaging at the free surface showed metastable vertical PMMA domain orientation on gold substrates. In contrast, horizontal orientation was obtained on oxide-coated silicon regardless of surface roughness and annealing conditions. The horizontal domain orientation on silicon substrates was ideal to probe simultaneously the difference in surface charge and hydrophilicity of the two distinct nanoscale domains of UV/AcOH treated PS-b-PMMA films. CFM on UV/acetic acid etched PS-b-PMMA revealed the presence of –COO- groups which were found to be more abundant inside the etched trenches than on the unetched PS matrix as shown by ferritin adsorption onto etched PS-b-PMMA. Lastly, the PS-b-PMMA was cast as a free-standing monolith at the end of a quartz micropipette. AFM revealed circular PMMA dots at the free surface, indicating alignment parallel to the long axis of capillary. Ion conductance within nanochannels indicated surface –charge governed ion transport at low KCl concentrations and flux of negatively-charged sulphorhodamine dye demonstrated the permselective nature of nanochannels.
Keywords: Diblock copolymer; Photolithography; Nanoscale structures; Nanochannels; Chemistry, Analytical (0486); Chemistry, Physical (0494)